The way of building modeling and caculation the dynamic of a 3D frame by finite element method - Nguyễn Hoài Sơn; Nguyễn Duy Hùng; Trần Thị trà Mi (Journal of Technical Education Science, 2013)
Analytic solutions are not meet for most practical cases. Thus, numerical method is an efficient tool which support strongly for these cases and the Finite Element Method (FEM) is one of the method which meet this requirement. In this paper, we present the way of building modeling and calculation the dynamic of a 3D Frame by Finite Element Method.